Land use change and farmer behavior in reclaimed land in the middle Jiangsu coast, China. (1st March 2017) - Cai, Fangfang; van Vliet, Jasper; Verburg, Peter H.; Pu, Lijie
Abstract: In order to find space for urban expansion and food production, China is rapidly converting its coastal wetlands through large-scale land reclamation. These conversions are dramatically altering the coastal environment, affecting the associated ecosystem services and threatening the regional ecological security. Since this trend is expected to continue for maintaining the economic growth and food security considerations, understanding the extent of reclamation and its related land use changes is important for sustainable coastal land use planning and management. In this study, we analyze land use changes between 1977 and 2015 in middle Jiangsu coast, China, an area that is characterized by land reclamation from wetland conversion. In addition, we surveyed local farmers occupying the reclaimed land and compared their farm characteristics and attitudes against their inland counterparts to understand their role in these processes. We observed that 17% of the reclaimed land was converted to farmland and 43% to aquaculture ponds during the study period. At the same time, the natural wetlands, which originally dominated the area, were substantially reduced by 96%. Characteristics of farmers cultivating the reclaimed land were relatively similar to the inland farmer in many aspects. However, coastal farmers owned larger farms with less fragmented parcels, have a higher income from their farm and showed more enthusiasms for implementing agricultural land use changes comparing to their inland counterparts. The environmental value of the coastal wetlands and the limited opportunities for further land reclamation will pose significant challenges in the context of the region being a hotspot of urban expansion and an important contributor to food production. Highlights: We analyze land use changes in reclaimed coastal wetlands in China between 1977 and 2015. Natural wetlands are mainly converted into cropland after reclamation. Farmers of reclaimed land have larger and less fragmented farms, and a higher income from agricultural business. The trade-offs between coastal economic demands and natural protection require a sustainable land management strategy.